The Effect of Work-Life Balance and Workload on Job Satisfaction to Affect Nurse Performance - I Komang Oka Permadi; I Komang Suryadnya Diputra; Putu Ari Pertiwi Sanjiwani (Ekonomis: Journal of Economics and Business, 2023)
In the process of providing service, nurses are the most interactive healthcare personnel with patients. Nurses in public hospitals have a huge responsibility for providing quality health care. The study aims to confirm and re-test the impact of work-life balance and workload on job satisfaction and the performance of nurses. The sample determination uses the nonprobability sampling method with the technique of taking saturated samples (sensus), so that the entire population of 32 people is the sample. Path analysis is used to test hypotheses in research using SmartPLS version 3.2.9. The study revealed that work-life balance showed a significant positive impact on job satisfaction but no significant impact on nurses’ performance; the workload on an informed nurse’s job satisfaction can have an equally significant positive effect on the performance of the nurse; the satisfaction of the real job does not have a significant effect on the nurse's performance; and job satisfaction cannot affect the impact of work-life balances and workloads on the nurse's performance.